Metode Support Vector Machine (SVM) dan Lexicon-Based dalam Analisis Sentiment Ulasan Pengguna Aplikasi Wink - Syahrudin, Syahrudin; Fenilinas Adi Artanto; Ahmad Rifqi Maulana; Filsafat, Filsafat (Yayasan Literasi Sains Indonesia, 2025)
Sentiment Sentiment Analysis is an important method in understanding user opinions of an application. This study aims to analyze the sentiment of users of the Wink application on the Google Play Store, which is a popular application that uses Artificial Intelligence (AI) in photo and video editing that has many templates and is easy to use. Sentiment analysis was carried out using the Lexicon-Based approach and the Support Vector Machine (SVM) classification algorithm. Data was taken from reviews on the Google Play Store Wink Application which obtained 1905 review data showing that 78.6% of users gave a rating of 4 to the application, while the Lexicon-Based approach identified 69.5% of reviews with positive sentiment values ​​with many words that appear are